(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: The advances in biomedical technology that lead to an increase in early diagnosis and treatment have helped to increase the number of health breast cancer survivors in Indian as well as worldwide. Researches carried out on survivorship have focused mainly on the psychological impact and health outcome of the disease. The goal of this study was to focus on exploring the lived experiences of breast cancer survivors from diagnosis of the disease till the survivor life. Objective: To explore the lived experiences of women who are breast cancer survivors. Design, Setting and Participants: A purposive sampling strategy was used to recruit participants from amedical college hospital. A total of 18 women breast cancer survivors were interviewed. Findings: The study concluded with four major themes that described lived experiences of women. These were factors from the diagnosis and treatment of breast cancer impacting survivorship, support system and relationships, and issues in survivor life. All the participants noted that it was so stressful journey that they went through after diagnosis till the completion of various treatment modalities. Each one found their own way to cope with the stress. Support from family was shared as the key which gave them strength and courage through the different stages of treatment. However, they found it difficult to explain what survivorship meant. Conclusion: This study using in-depth interview techniques, shed light on the lived experiences of breast cancer survivors who have completed the treatment. All of them had fear and frustration during their diagnosis and treatment. They felt depressed due to body changes still the support they received from their partners and family helped them to come out of that feelings. However, they noted that they still live with the fear of recurrence of cancer.